Olaparib Induces RPL5/RPL11-Dependent p53 Activation via Nucleolar Stress - Han, Tao; Tong, Jing; Wang, Mengxin; Gan, Yu; Gao, Bo; Chen, Jiaxiang; Liu, Youxun; Hao, Qian; Zhou, Xiang (Frontiers in Oncology, 2022)
The poly(ADP-ribose) polymerase (PARP) inhibitor (PARPi) Olaparib is a widely used targeted therapy for a variety of solid tumors with homologous recombination deficiency (HRD) caused by mutation of BRCA1/2 or other DNA repair genes. The anti-tumor activity of Olaparib has been largely attributed to its ability to inhibit PARP enzymes and block DNA single-strand break (SSB) repair, which eventually leads to the most detrimental DNA damage, double-strand breaks (DSB), in HRD cells. Although PARPi was found to induce p53-dependent cell death, the underlying molecular mechanism remains incompletely understood. Here, we report that Olaparib treatment leads to p53 stabilization and activation of its downstream target genes in a dose- and time-dependent manner. Mechanistically, Olaparib triggers nucleolar stress by inhibiting biosynthesis of the precursor of ribosomal RNAs (pre-rRNA), resulting in enhanced interaction between ribosomal proteins (RPs), RPL5 and RPL11, and MDM2. Consistently, knockdown of RPL5 and RPL11 prevents Olaparib-induced p53 activation. More importantly, Olaparib efficiently suppresses breast and colorectal cancer cell survival and proliferation through activation of p53. Altogether, our study demonstrates that Olaparib activates the nucleolar stress-RPs-p53 pathway, suggesting rRNA biogenesis as a novel target for PARPi.